VD_FINDINFO Jug / 2014 / 9 vom 25. Juni 2013 - VD Tribunal cantonal (2013)
NÉGLIGENCE, PRINCIPE DE LA CONFIANCERÈGLE DE LA CIRCULATION, CAUSALITÉ NATURELLE | 12 al. 3 CP, 125 al. 1 CP, 26 al. 1 LCR, 31 al. 1 LCR, 428 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH)